2011
DOI: 10.1177/0363546511419822
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral Muscle Activation During Provocative Tests Designed to Diagnose Superior Labrum Anterior-Posterior Lesions

Abstract: Background Despite considerable medical advances, arthroscopy remains the only definitive means of Superior Labrum Anterior-Posterior (SLAP) lesion diagnosis. Natural shoulder anatomic variants limit the reliability of radiographic findings and clinical evaluations are not consistent. Accurate clinical diagnostic techniques would be advantageous due to the invasiveness, patient risk, and financial cost associated with arthroscopy. Purpose The purpose was to examine the behavior of the joint stabilizing muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The highest activity for infraspinatus was seen in Wood et al 22 during the active compression test, palms down, for SLAP tears (182%MVIC). This test involves the participant standing with the shoulder flexed to 90u u and adducted 10-15u u medial to the sagittal plane, the elbow fully extended.…”
Section: Infraspinatus Activitymentioning
confidence: 83%
“…The highest activity for infraspinatus was seen in Wood et al 22 during the active compression test, palms down, for SLAP tears (182%MVIC). This test involves the participant standing with the shoulder flexed to 90u u and adducted 10-15u u medial to the sagittal plane, the elbow fully extended.…”
Section: Infraspinatus Activitymentioning
confidence: 83%
“… 12 However, biomechanically one would expect an opposite result to the test as the tensile load onto the tendon of the long head biceps is increased in external rotation of the shoulder, when one expects a pain relieve during the second part of the test. 7 , 21 Green et al suggested that this failure to support its proposed anatomic basis may partly explain the variable likelihood ratios obtained in clinical accuracy studies of the O'Brien test. 5 , 7 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Moreover, based upon our clinical experience and recent biomechanical data, we hypothesized that the O’Brien test would be the most predictive of posteroinferior labral tears. 7 , 15 , 21 Therefore, the primary aim was to determine the diagnostic value of the O’Brien test in localizing labral tears of the shoulder.…”
mentioning
confidence: 99%
“…A simple, electronic search of the literature between 2011 and 2013 found over 20 papers reporting LD activity recorded with the use of surface electrodes. The scope of these studies ranged from investigating LD activity during: normal shoulder function (Hawkes et al, 2012b;Rota et al, 2013); various sporting activities including rowing (Bazzucchi et al, 2013), tennis (Rota et al, 2012), pole vaulting (Frere et al, 2012), skiing (Nilsson et al, 2013), baseball (Reyes et al, 2011), golf (Lim et al, 2012) and swimming (Ikuta et al, 2012); exercises (Marchetti and Uchida, 2011); shoulder and trunk dysfunction (Hawkes et al, 2012a;Ntousis et al, 2013;Wood et al, 2011); classical singing (Watson et al, 2012); and muscle fatigue (Balasubramanian et al, 2014).…”
Section: Introductionmentioning
confidence: 99%